JARINGAN SOSIAL PETANI: UPAYA PETANI PEMULA DALAM MEMBANGUN JARINGAN SOSIAL UNTUK MENGAKSES SUMBERDAYA USAHATANI - Gema Wibawa Mukti; Rani Andriani Budi Kusumo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
This paper aims to explore how social networks provide farmers with access to resources, understanding the extent to which farmers with agricultural and non-agricultural backgrounds build their business networks. The research methodology is qualitative. Data was collected between October 2020 – June 2021, through semi-structured interviews with 30 farmers in West Java. There are 15 farmers who have an agricultural background, and 15 of them are novice farmers who do not have an agricultural background. The results showed that strong and weak ties each contributed to novice farmers in accessing resources. Beginner farmers who are not from the agricultural environment struggle harder to build business networks, making greater sacrifices in accessing the resources they need. Farmers with non-agricultural backgrounds are able to access material resources which are usually obtained from strong social ties. With hard effort and sacrifice, they are able to get resources from weak social ties. Agriculture is a sector that is constantly undergoing rapid changes, so these two groups of farmers must be able to move quickly, across “borders” to access resources in innovative ways from various existing sources.